Pengaruh Metode Latihan Drill Dan Koordinasi Mata Tangan Terhadap Forehand Dan Backhand Drive Tenis Lapangan - Trisna Wati, Ni Ketut Widhi; Sudiana, I K; Iwan Swadesi, I K; Wahjoedi, H; Yoda, I K (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
This study aims to analyze (1) the differences in forehand and backhand drive strokes between field tennis athletes who received training using the drill massed practice training method and those who received training using the distributed practice training method, (2) the influence of the interaction between training methods and hand eye coordination on forehand and backhand drive strokes, (3) differences in forehand and backhand drive strokes between field tennis athletes who receive training using the drill massed practice training method and field tennis athletes who are trained using the distributed practice training method in field tennis athletes who have high hand eye coordination, (4) differences in forehand and backhand drive strokes between field tennis athletes who received training using the drill massed practice training method and field tennis athletes who were trained using the distributed practice training method in field tennis athletes who have low hand eye coordination. This type of research is quasi-experimental research with a Posttest Only Non-Equivalent Control Group Design. The population of this study is all tennis athletes assisted by PELTI Buleleng Regency in 2023 with a total population of 44 tennis athletes. The total sample in the study was 44 tennis athletes selected using the ordinal pairing technique. The data collected in this research is in the form of forehand and backhand drives. Forehand and backhand drive data were collected with Hewitt's achievement test. Data analysis was carried out using descriptive statistics and 2-way MANOVA test. The results of the research show that, (1) there are differences in forehand and backhand drive strokes between field tennis athletes who received training using the drill massed practice training method and those who received training using the distributed practice training method (F = 6.829; p<0.05), ( 2) there is an interaction effect between training method and hand eye coordination on forehand and backhand drive strokes (F = 5.512; p<0.05), (3) there are differences in forehand and backhand drive strokes between field tennis athletes who receive training using the training method drill massed practice and field tennis athletes who were trained using the distributed practice training method for field tennis athletes who had high hand eye coordination (F = 5.568; p<0.05), as well as (4) differences in forehand and backhand drive strokes between field tennis athletes who received training using the drill massed practice training method and field tennis athletes who were trained using the distributed practice training method for field tennis athletes who had low hand eye coordination (F = 6.570; p<0.05).